Training general practitioners contributes to the identification of palliative patients and to multidimensional care provision: secondary outcomes of an RCT - Thoonsen, Bregje (BMJ Support Palliat Care, 2019)
INTRODUCTION: To support general practitioners (GPs) in providing early palliative care to patients with cancer, chronic obstructive pulmonary disease or heart failure, the RADboud university medical centre indicators for PAlliative Care needs tool (RADPAC) and a training programme were developed to identify such patients and to facilitate anticipatory palliative care planning. We studied whether GPs, after 1 year of training, identified more palliative patients, and provided multidimensional and multidisciplinary care more often than untrained GPs. METHODS: We performed a survey 1 year after GPs in the intervention group of an RCT were trained. With the help of a questionnaire, all 134 GPs were asked how many palliative patients they had identified, and whether anticipatory care was provided. We studied number of identified palliative patients, expected lifetime, contact frequency, whether multidimensional care was provided and which other disciplines were involved. RESULTS: Trained GPs identified more palliative patients than did untrained GPs (median 3 vs 2; p 0.046) and more often provided multidimensional palliative care (p 0.024). In both groups, most identified patients had cancer. CONCLUSIONS: RADPAC sensitises GPs in the identification of palliative patients. Trained GPs more often provided multidimensional palliative care. Further adaptation and evaluation of the tools and training are necessary to improve early palliative care for patients with organ failure. TRIAL REGISTRATION NUMBER: NTR2815; post results.